Pengaruh Price Discount dan Hedonic Shopping Motivation terhadap Impulse Buying - Dilla Kristanty; Mahani, Septiana Ayu Estri (Bandung Conference Series: Business and Management, 2024)
Abstract. This research is based on increasingly tight competitive conditions in the business world and very rapid advances in internet technology. In the current development of the modern world and globalization, the internet can provide information related to many things very quickly, especially in digital technology such as the use of e-commerce which is increasingly embedded in everyday life, giving rise to a new lifestyle in fulfilling needs and desires by shop online. Business strategies are created to fulfill consumer lifestyles, thereby creating encouragement for consumers to carry out impulse buying. The aim of this research is to analyze the influence of Price Discount and Hedonic Shopping Motivation on Impulse Buying (Study on the 3second Official Website in Bandung City). This type of research is included in descriptive and verification research with quantitative methods. This research was conducted by distributing questionnaires to 120 respondents. The sampling technique used is non-probability sampling. The analytical method used is multiple linear regression analysis with the help of SPSS 25 software, hypothesis testing using the T Test and F Test. The research results show that partial Price Discount does not have a significant effect on Impulse Buying. Hedonic Shopping Motivation partially has a significant effect on Impulse Buying. And Price Discount and Hedonic Shopping Motivation simultaneously have a significant effect on Impulse Buying (Study on the 3second Official Website in Bandung City). Abstrak. Penelitian ini didasarkan pada kondisi persaingan dalam dunia bisnis yang semakin ketat serta kemajuan teknologi internet yang sangat pesat. Dalam perkembangan dunia modern dan globalisasi seperti saat ini, internet dapat memberikan informasi terkait banyak hal dengan waktu yang sangat cepat khususnya pada teknologi digital seperti penggunaan e-commerce yang semakin melekat dalam kehidupan sehari-hari sehingga menimbulkan gaya hidup baru dalam memenuhi kebutuhan dan keinginan dengan berbelanja secara online. Strategi bisnis dibuat untuk memenuhi gaya hidup yang konsumtif sehingga menciptakan dorongan pada konsumen untuk melakukan impulse buying. Tujuan penelitian ini adalah untuk menganalisis pengaruh Price Discount dan Hedonic Shopping Motivation terhadap Impulse Buying (Studi pada Official Website 3second di Kota Bandung). Jenis penelitian ini termasuk dalam penelitian deskriptif dan verifikatif dengan metode kuantitatif. Penelitian ini dilakukan dengan menyebarkan kuesioner kepada 120 responden. Teknik sampling yang digunakan adalah non-probability sampling. Metode analisis yang digunakan adalah analisis regresi linear berganda dengan bantuan software SPSS 25, uji hipotesis menggunakan Uji T dan Uji F. Hasil penelitian menunjukan bahwa Price Discount secara parsial tidak berpengaruh signifikan terhadap Impulse Buying. Hedonic Shopping Motivation secara parsial berpengaruh signifikan terhadap Impulse Buying. Serta Price Discount dan Hedonic Shopping Motivation secara simultan berpengaruh signifikan terhadap Impulse Buying (Studi pada Official Website 3second di Kota Bandung).